Implementasi Metode Simple Additive Weighting (SAW) dalam Pemilihan Sekolah Ramah Anak - Sulistiawati Rahayu Ahmad; Salim M; Salma PNua (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Child-Friendly School is a program aimed at achieving safe, clean, healthy, caring, and environmentally conscious conditions that ensure the fulfillment of children's rights and protection from violence, discrimination, and other forms of mistreatment while they are in educational institutions. It also supports children's participation, particularly in planning, policies, learning, and supervision. One of the objectives of developing the Child-Friendly School Policy is to fulfill, guarantee, and protect children's rights, as well as to ensure that educational institutions can develop children's interests, talents, and abilities, and prepare them to be responsible for a tolerant, respectful, collaborative life for progress and a spirit of peace. The research aims to design a Web-based Decision Support System for Selecting Child-Friendly Schools in the Education Office of Gorontalo City using the Simple Additive Weighting (SAW) method. The research adopts the Waterfall method as the research approach and conducts Whitebox and Blackbox testing for the system. The research findings indicate that the system can facilitate schools applying for child-friendly school certification from the Education Office of Gorontalo City. It provides a transparent ranking output based on the assessment of predetermined criteria weights. The system can perform quick, accurate, and precise weighting calculations using the SAW decision support method, and it provides information on the suitability status based on the weight values derived from the matrix summation after the 'SAW method' button is processed